2016
DOI: 10.1007/s00335-016-9659-2
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted autophagy undermines skeletal muscle adaptation and integrity

Abstract: This review assesses the importance of proteostasis in skeletal muscle maintenance with a specific emphasis on autophagy. Skeletal muscle appears to be particularly vulnerable to genetic defects in basal and induced autophagy, indicating that autophagy is co-substantial to skeletal muscle maintenance and adaptation. We discuss emerging evidence that tension-induced protein unfolding may act as a direct link between mechanical stress and autophagic pathways. Mechanistic links between protein damage, autophagy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 121 publications
(164 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, similar to our observations, another investigation found that 8 weeks of resistance ladder training under normoxia reduces the LC3II/LC3I ratio and elevates the level of p62 [42]. Thus, regular long-term repetitive training may increase the threshold for activation of autophagy by stress, thereby protecting the muscle [43][44][45].…”
Section: Resistance Training Alleviates Hypoxia-induced Muscle Atrophsupporting
confidence: 86%
“…Furthermore, similar to our observations, another investigation found that 8 weeks of resistance ladder training under normoxia reduces the LC3II/LC3I ratio and elevates the level of p62 [42]. Thus, regular long-term repetitive training may increase the threshold for activation of autophagy by stress, thereby protecting the muscle [43][44][45].…”
Section: Resistance Training Alleviates Hypoxia-induced Muscle Atrophsupporting
confidence: 86%
“…Autophagy plays an important function in skeletal muscle maintenance by regulating protein homeostasis, and impaired autophagy disrupts the fitness and integrity of skeletal muscles [26]. We found that CSRP3 regulates basal autophagy and exerts a beneficial role in chicken primary myoblasts.…”
Section: Discussionmentioning
confidence: 79%
“…In healthy cells potentially harmful cellular contents such as protein aggregates or damaged organelles are eliminated by selective autophagy. Defective autophagic processes result in poor protein quality control, limited availability of free amino acids, disrupted metabolic homeostasis and inefficient stress response triggering compensatory mechanisms that lead to excess autophagy (38). Altered, upregulated autophagy involves a decline in the selectiveness of this process that now takes place in an indiscriminate manner (16), in line with the phenotype of vacuolar myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…In these disorders, normal, tightly regulated autophagy is disturbed, leading to the accumulation of autophagic substrate in large, membrane‐bound vacuoles. Muscle fibers are particularly susceptible to alterations of autophagy, because they constantly accumulate autophagic substrate caused by high protein turnover and exposure to mechanical stress (38). In addition, dysfunctional mitochondria that undergo mitophagy accumulate at high numbers in muscle fibers during aging (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation